2004
DOI: 10.1088/0953-2048/17/10/r01
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural parameters and superconducting properties of 1201-type (Hg,M)Sr2CuO4+ (M = Cr, Mo or Re): an overview

Abstract: A brief overview of the current state of development of 1201-type, Ba-free, mercury cuprates, (Hg, M)Sr 2 CuO 4+δ (M = Cr, Mo or Re), is presented. Our focus here is confined to synthesis methods, chemical stabilization, structural parameters and superconducting properties of this Hg/Sr 1201 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…X-ray diffraction analysis revealed that (Hg, Cr)/Sr-1201 samples had tetragonal crystal symmetry with lattice parameters a = 3.840-3.854 Å and c = 8.639-8.705 Å that slightly varied with 'x'. Following Shimoyama et al [1], various groups [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have reported a maximum T onset c ∼ 58 K and T (R=0) c ∼ 51-56 K for the composition (Hg 0.7 Cr 0.3 )Sr 2 CuO 4+δ . Chmaissem et al [4] have reported a high T onset c of ∼67 K in the assynthesized (Hg, Cr)/Sr-1201 sample that subsequently, on oxygen annealing, reduced the T onset c to ∼58 K. The fall in T c was attributed to hole overdoping [4], which was strongly contested by other groups [8,9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction analysis revealed that (Hg, Cr)/Sr-1201 samples had tetragonal crystal symmetry with lattice parameters a = 3.840-3.854 Å and c = 8.639-8.705 Å that slightly varied with 'x'. Following Shimoyama et al [1], various groups [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have reported a maximum T onset c ∼ 58 K and T (R=0) c ∼ 51-56 K for the composition (Hg 0.7 Cr 0.3 )Sr 2 CuO 4+δ . Chmaissem et al [4] have reported a high T onset c of ∼67 K in the assynthesized (Hg, Cr)/Sr-1201 sample that subsequently, on oxygen annealing, reduced the T onset c to ∼58 K. The fall in T c was attributed to hole overdoping [4], which was strongly contested by other groups [8,9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%